Trend in post-mortem uptake for stillbirths and neonatal deaths, england, wales, northern ireland and the crown dependencies, 2000–2009. (7th June 2011) - Springett, A; Dorling, J; Stephens, I; Golightly, S
Abstract : Background and aims: Post-mortems (PM) are an important technique for understanding and learning from stillbirths (SB) and neonatal deaths (NND) that should be offered to all parents. The retention of organs in UK hospitals publicised in the late 1990s reduced the uptake by parents and introduced paperwork and procedures that may have inhibited health professionals from seeking consent. Methods: Data on all SBs and NNDs across England, Wales, Northern Ireland and the Crown Dependencies were collected from 2000 to 2009 by a network of CMACE local coordinators using a standard form. Whether a PM was offered and consented to was routinely collected for all. Results: The percentage of PMs being performed for SBs and NNDs has significantly decreased (p<0.001). In 2000 PMs were performed for 55% of SBs and 23% of NNDs dropping to 45% and 13% respectively in 2009. This appears to be due to an increase in the percentage of parents who did not wish to consent for a PM (p<0.001). For cases of SB and NND, this has occurred despite an increase in the percentage of parents being offered a PM (p<0.001). The percentage of NNDs being referred to the coroner has also increased from 8% to 17% (p<0.001) but no significant change was seen for SBs. Conclusion: There has been a reduction in the proportion of perinatal deaths being assessed by PM. This, coupled with reducing perinatal mortality, may have implications for the maintenance of pathology skills and supports the centralised service provided for these.